High prevalence of carbapenem and extended spectrum β-lactam resistant Escherichia coli from tilapia (Oreochromis niloticus) from two wet markets in Metro Manila, Philippines - Kang, Taeuk (Animo Repository, 2020)
Aim: Multiple drug resistant bacteria are serious health problems worldwide, with carbapenem resistant and extended spectrum-β-lactamase (ESBL) producing Enterobacteriaceae classified by Centers for Disease Control and Prevention under the category of "Urgent Threats" and "Serious Threats", respectively. The study characterized Escherichia coli from Oreochromis niloticus procured from two wet markets in Metro Manila in January and September 2016 for their drug resistance. Methodology and results: Antimicrobial susceptibility profiles were determined using standard disc diffusion method. Extended-spectrum β-lactamase production was confirmed using clavulanate double disc synergy assay, carbapenemase production was tested using modified Hodge test, and MBL (metallo-β-lactamase) production was tested using EDTA double disc synergy assay. Results show that of the 25 isolated E. coli, 24 or 96% were resistant to at least one antimicrobial, with 60% being multiple drug resistant. These strains exhibited 20 different resistance phenotypes, suggesting these were different strains. Fifteen of the isolates (60%) screened positive for ESBL. Among these, 11 lost their resistance, indicating the instability of the resistance genes in the host, a characteristic of plasmid-mediated ESBL production. The ESBL suspects tested were confirmed to be ESBL producers. A high 48% of isolates were found to be resistant to carbapenems, with eight of the 11 tested (73%) being positive for carbapenemase production. MBL positive isolates carried the blaIMP gene as determined by multiplex PCR and nucleotide sequencing. Conclusion, significance and impact of study: Study showed a high prevalence of multiple drug resistant E. coli isolates from the commonly-consumed Tilapia procured from the wet markets. This result is compounded by the alarmingly high prevalence of carbapenem resistant and ESBL-producing strains among these isolates. Considering that the genes coding for these resistances are found in mobile genetic elements such as plasmids and integrons that can be transferred to other bacteria resulting to a rapid increase in drug resistant strains, it is highly imperative for all the concerned government units to establish a well-coordinated national surveillance program to monitor and address the occurrence and increase in drug resistant microorganisms in man, animals and the environment. In addition, prudent use of antimicrobials among these should be seriously instituted. © 2020 Universiti Sains Malaysia.